Wild Rosa L. taxa of the National Nature Park ‘Podilskyi Tovtry’ (Podolian Hills, Western Ukraine) - Sołtys-Lelek, Anna; Oliіar Halyna (Biodiversity: Research and Conservation, 2016)
The present paper discusses the wild roses of the National Nature Park ‘Podilskyi Tovtry’. The purpose of the work was to compile a full list of the wild Rosa taxa growing in the study area and present their distribution. Based on the field studies during the years 2009-2013 and published data, 20 taxa have been recorded, among them: 16 native species (including three hybrids with the rank of species), 2 anthropophytes and 2 hybrids. However, the taxonomical status of Rosa caryophyllacea Besser is not clear and species requires taxonomical revision. Three new rosa species for the Park were found during the studies. These are: Rosa micrantha, R. ×subcanina and R. ×subcollina. The list of the roses occurring in this area is still far away from being completed, therefore, further research is needed.